Hemodynamic impairment of double culprit ST-elevation myocardial infarction, double the trouble: a case report - Asaf, Mikhael; Afandy, Jonathan Edbert; Danny, Siska Suridanda (The Indonesian Heart Association, 2025)
Background: Multiple culprit artery involvement is rare (2.5%) among ST-segment elevation myocardial infarction (STEMI) patients undergoing primary coronary intervention (PCI). It can occur due to multiple factors and reflects a widespread pathophysiologic process. Most patients present with unstable hemodynamics and cardiogenic shock (CS), which results in a high mortality rate. Currently, there are no guidelines or consensuses on the management of multiple culprit arteries in STEMI patients. Case Illustration: A 51-year-old man with chest pain in the past 16 hours was referred to the National Cardiovascular Center Harapan Kita. ECG at presentation revealed sinus rhythm with ST elevation in the inferior, posterior, and right leads. He was diagnosed with late-onset infero-posterior STEMI + right ventricle infarction, Killip IV, and thrombolysis in myocardial infarction 6/14, then was prepared for early PCI due to ongoing chest pain and CS. The patient underwent complete revascularization with drug-eluting stents and thrombus aspiration due to the high thrombus burden of the lesion in the right coronary artery and first obtuse marginal artery. After early PCI, his hemodynamic condition improved, and epigastric pain was his only complaint. However, on the following day, the patient experienced acute pulmonary edema and rhythm conversion to total AV block. He was managed conservatively with heparinization, inotropes, vasopressors, diuretics, and noninvasive ventilation. After 14 days of hospitalization, the patient was discharged without any complaints. Conclusion: Double culprit STEMI is rare and associated with catastrophic hemodynamic impairment, including CS, at presentation. Individualized treatment with early and aggressive revascularization yields relatively good results.